Using the Art Museum as a Bridge to the Future - Šola, Tomislav (2004)
The museum's tasks: fulfilling the great expectations of the society as the answer to decisions taken by the society, start a discussion about the role of the museums in the society to map our possibilities and necessities, to reform the system and to keep it active at the same time.
Projekt MZOS
ENG